Watercolor techniques for artists & illustrators - Douglass, Megan; DK Publishing, Inc. (DK, 2020)
Challenging aspiring artists to challenge themselves and try new things, this art instruction book, in which professional artists demonstrate every aspect of their craft, shows how to master all the techniques of watercolor. Illustrations.
Whether you're getting started in watercolor painting, or looking to advance your range of skills, this book will help you take a comprehensive, in-depth look at techniques to expand your repertoire. The artists and illustrators work across a range of styles to equip you with the skills and confidence to develop your own style and grow as an artist. -- adapted from jacket
The basics -- Techniques. Introduction ; Beginner techniques ; Intermediate techniques ; Advanced techniques -- Subjects. Introduction ; Landscapes and townscapes ; Patterns, still lifes, and flowers ; Portraits, figures, and animals.
"Discover how to paint landscapes, people, still lifes, and more" -- Cover.
"Develop your own style, guided by professionals"--Cover
Includes index.
Keywords: Watercolor painting -- Technique; Watercolor painting -- Technique; Instructional and educational works; Instructional and educational works